Application of Montgomery T-Tube Placement in Treating Cotton-Myer IV Subglottic Airway Atresia after Bi-Level Airway Recanalization. (28th May 2021) - Wu, Fengjie; Yao, Yangwei; Gu, Yangyang; Yang, Meng; Chen, Enguo; Hu, Huihui; Zhang, Jisong; Dong, Liangliang; Zhu, Yeli
Abstract : Objective. The purpose of this study is to explore the effectiveness and safety of Montgomery T- tube placement in treating Cotton-Myer IV subglottic airway atresia after bi-level airway recanalization. Methods. This study is a retrospective study. 11 patients who were treated for IV subglottic airway atresia between January 2017 and January 2019 in the Second Affiliated Hospital of Jiaxing University were involved in this study. The 11 patients all had undergone tracheotomies at our hospital, and they were transferred to the Department of Pulmonary and Critical Care Medicine for Montgomery T- tube placement after bi-level airway recanalization when their subglottic airway was atretic. Patients were observed for their clinical manifestations after placement. The effectiveness of T- tube placement after bi-level airway recanalization was assessed. The incidence of short-term and long-term complications after surgery was assessed. Patients were followed up for 3 to 24 months for evaluating their airway recovery. Results. T- tubes were successfully placed in 11 patients. The atretic airways of all patients were recanalized after treatment. Eight patients got restoration of vocal ability, and 3 patients could only say simple words. None of the patients needed assisted oxygen inhalation. The SpO2 average level was increased from 95 ± 2 % before treatment to 97 ± 3 % after treatment. Patients had significant relief of cough or sputum, and they had less difficulty in dyspnea. All short- or long-term complications were self-relieved or controlled without further malignant progression after treatment by doctors. The average postoperative extubating time was (14.86 ± 3.62 ) months. Conclusion. The application of Montgomery T- tube placement in treating Cotton-Myer IV subglottic airway atresia after bi-level airway recanalization is well effective and safe for patients, and it can be promoted in clinical treatment.